Dollarization, Inflation Targeting, and Inflationary Dynamics in Ghana. Issue 3 (3rd July 2019) - Tweneboah, George; Alagidede, Paul
ABSTRACT: The impact of dollarization on domestic economic performance, and the welfare implications of high inflation in an inflation targeting environment, have remained a matter of much concern for policymakers in recent years. This study investigates the effects of dollarization on inflation and inflation uncertainty in Ghana for the period January 1990 to December 2017. We apply the exponential Generalized Autoregressive Conditional Heteroskedasticity model together with impulse response and Granger causality tests to explore how dollarization affects the behavior of inflation for the pre-inflation targeting period (January 1990 – May 2007) and post-inflation targeting period (June 2007 – December 2017). The results indicate that dollarization has not played a significant role in the volatility of inflation in Ghana. Also, inflation Granger causes dollarization in both the pre- and post-inflation targeting regimes. Finally, there is a bidirectional causal relationship between inflation and inflation uncertainty following the adoption of inflation targeting monetary policy. We conclude that, although inflation targeting has not presented a significant impact on inflation volatility, it has affected the relationship between inflation and inflation uncertainty in Ghana. The dynamics of inflation volatility and asymmetries present crucial implications which are discussed to guide policymaking.